Study of 99mTc Pertechnetate Radiopharmaceuticals in Relation to Thyroid Hormone for Toxic and non-Toxic Diffuse Goiter - N.P. Viantri; W. Setiabudi; C. Anam; F. Nadzir; C. Varuna (PPIKSN-BATAN, 2012)
Abnormalities of the thyroid gland in the form of enlargement of the thyroid gland are called a goiter. Goiter is divided into two types, namely toxic and non-toxic diffuse goiter. Diagnosis could be done with thyroid scan (in vivo) and test for thyroid hormone value (in vitro). Thyroid scan is applied by giving injection of 99mTc Pertechnetate as much as 2 - 5 mCi intravenally in the arm and then thyroid gland and salivary glands imaging were conducted in the fifth minute, tenth minute and fifteenth minute using gamma camera. Thyroid hormones test in blood is done with radioimmunoassay method. The same pattern showed the accumulation polad of the radioactive number from quotation of salivary glands. The accumulation percentage activity of 99mTc Pertechnetate in thyroid gland for the case of toxic diffuse goiter is larger than the case of non-toxic diffuse goiter. The results of this study indicate that the predictors for the case of toxic diffuse goiter could be characterized by high thyroid uptake which the the value of T3 hormone ≥ 3.3 ng/dl, the value of T4 hormone ≥ 165 nmol/l, and the value of TSH hormone ≤ 0.2 μIU/ml. While the case of non-toxic diffuse goiter could be characterized by low thyroid uptake which the value of T3 hormone ≥ 1.2 ng/dl, the value of T4 hormone ≥ 90 nmol/l, and the value of TSH hormone ≤ 1.8 μIU/ml. Received: 14 November 2011; Revised: 18 April 2012; Accepted: 21 April 2012